S-1-based chemotherapy versus capecitabine-based chemotherapy as first-line treatment for advanced gastric carcinoma: a meta-analysis. - Ming-ming He (Public Library of Science (PLoS), 2013)
Background Although both oral fluoropyrimidines were reported effective and safe, doubts exist about whether S-1 or capecitabine is more advantageous in advanced gastric carcinoma (AGC). Herein, we performed a meta-analysis to comprehensively compare the efficacy and safety of S-1-based chemotherapy versus capecitabine-based chemotherapy as first-line treatment for AGC. Methods PubMed/Medline, EmBase, Cochrane library, and China National Knowledge Infrastructure databases were searched for articles comparing S-1-based chemotherapy to capecitabine-based chemotherapy for AGC. Primary outcomes were overall response rate (ORR), time to progression (TTP), overall survival (OS), progression-free probability, and survival probability. Secondary outcomes were toxicities. Fixed-effects model were used and all the results were confirmed by random-effects model. Results Five randomized controlled trials and five cohort studies with 821 patients were included. We found equivalent ORR (38.3% vs. 39.1%, odds ratio [OR] 0.92, 95% conﬁdence interval [CI] 0.69-1.24, P = 0.59), TTP (harzad ratio [HR] 0.98, 95% CI 0.82-1.16, P = 0.79), OS (HR 0.99, 95% CI 0.87-1.13, P = 0.91), progression-free probability (3-month OR 1.02, 95% CI 0.62-1.68, P = 0.94; 6-month OR 1.34, 95% CI 0.88-2.04, P = 0.18) and survival probability (0.5-year OR 0.90, 95% CI 0.61-1.31, P =0.57; 1-year OR 0.97, 95% CI 0.70- 1.33, P = 0.84; 2-year OR 1.15, 95% CI 0.61-2.17, P = 0.66). Equivalent grade 3 to 4 hematological and non-hematological toxicities were found except hand-foot syndrome was less prominent in S-1-based chemotherapy (0.3% vs. 5.9%, OR 0.19, 95% CI 0.06-0.56, P = 0.003). There're no significant heterogeneity and publication bias. Cumulative analysis found stable time-dependent trend. Consistent results stratified by study design, age, regimen, cycle, country were observed. Conclusion S-1-based chemotherapy was associated with non-inferior antitumor efficacy and better safety profile, compared with capecitabine-based therapy. We recommended S-1 and capecitabine can be used interchangeably for AGC, at least in Asia.